3D-Printed COVID-19 immunosensors with electronic readout - Muñoz, Jose; Pumera, Martin (Chemical engineering journal (Lausanne, Switzerland, 2021)
3D printing technology has brought light in the fight against the COVID-19 global pandemic event through the decentralized and on-demand manufacture of different personal protective equipment and medical devices. Nonetheless, since this technology is still in an early stage, the use of 3D-printed electronic devices for antigen test developments is almost an unexplored field. Herein, a robust and general bottom-up biofunctionalization approach via surface engineering is reported aiming at providing the bases for the fabrication of the first 3D-printed COVID-19 immunosensor prototype with electronic readout. The 3D-printed COVID-19 immunosensor was constructed by covalently anchoring the COVID-19 recombinant protein on a 3D-printed graphene-based nanocomposite electrode surface. The electrical readout relies on impedimetrically monitoring changes at the electrode/electrolyte interface after interacting with the monoclonal COVID-19 antibody via competitive assay, fact that hinders the redox conversion of a benchmark redox marker. Overall, the developed 3D-printed system exhibits promising electroanalytical capabilities in both buffered and human serum samples, displaying an excellent linear response with a detection limit at trace levels (0.5 ± 0.1 μg·mL-1). Such achievements demonstrate advantage of light-of-speed distribution of 3D printing datafiles with localized point-of-care low-cost printing and bioelectronic devices to help contain the spread of emerging infectious diseases such as COVID-19. This technology is applicable to any post-COVID-19 SARS diseases.
Keywords: Surface engineering; Electrochemical detection; 3D-printed electrodes; Antigen test; SARS-CoV-2